Discovery of Giant Positive Magnetoresistance in Proximity to Helimagnetic Order in Manganese Phosphide Nanostructured Films - Mudiyanselage, Nivarthana W.Y.A.Y.; DeTellem, Derick; Chanda, Amit; Duong, Anh Tuan; Hsieh, Tzung En; Frisch, Johannes; Bär, Marcus; Madhogaria, Richa Pokharel; Mozaffari, Shirin; Arachchige, Hasitha Suriya; Mandrus, David; Srikanth, Hariharan; et al. (ACS Applied Materials and Interfaces, 2025)
The study of magnetoresistance (MR) phenomena has been pivotal in advancing magnetic sensors and spintronic devices. Helimagnets present an intriguing avenue for spintronics research. Theoretical predictions suggest that MR magnitude in the helimagnetic (HM) regime surpasses that in the ferromagnetic (FM) regime by over an order of magnitude. However, in metallic helimagnets like MnP, MR in the HM phase remains modest (<10%), limiting its application in MR devices. Here, a groundbreaking approach is presented to achieve a giant low-field MR effect in nanostructured MnP by leveraging confinement and strain effects along with spin helicity. Unlike the modest MR observed in bulk MnP single crystals and large-grain polycrystalline films, which exhibit a small negative MR in the FM region (∼2%) increasing to ∼8% in the HM region across 10-300 K, a grain size-dependent giant positive MR (∼90%) is discovered near FM to HM transition temperature (TN ∼ 110 K), followed by a rapid decline to a negative MR below ∼55 K in MnP nanocrystalline films. These findings illuminate a strain-mediated spin helicity phenomenon in nanostructured helimagnets, presenting a promising pathway for the development of high-performance MR sensors and spintronic devices through the strategic utilization of confinement and strain effects.
CRIS-Team Scopus Importer:2025-04-25
Keywords: helimagnets; magnetic sensors; magnetoresistance; MnP nanostructures; spintronics; strain effect; thin films